Perancangan Interior Fashion Store Local Brand di Banjarmasin - Desy Sastraho; Sriti Mayang Sari; M. Taufan Rizqy (Intra, 2016)
“Fashion Store Local Brand” in Banjarmasin is opened to fasilitate the increasing interest of local brand by adopting the local culture into deign. The design is referring to Banjarmasin‟s local culture, the character of Puteri Junjung Buih as a leader as Banjar‟s Kingdom. With the middle-up target market, “fashion store local brand” is designed modern and luxurious. The interior elements represent the character of Putri Junjung Buih, using „Sasirangan‟ fabrication which is Putri Junjung Buih‟s individual clothing style. The design theme “Magnificent Queen” is applicated using post-modern dramatic style. It fits to give luxurious look to the fashion store.